An animal model for febrile seizure induction using hot water bath - Mohamad Javad Saeedi Borujeni; Ghasem Sazegar; Seyyed Mojtaba Mousavi; Javad Hami; Hossein Haghir; Fatemeh Alipour (مجله دانشگاه علوم پزشکی بیرجند, 2013)
Background and Aim: Animal models offer an opportunity to induce febrile seizures in laboratories to assess the effects of neonatal fever and seizure on the central nervous system CNS). The present study aimed at introducing a method for febrile seizure induction in newborn rats. Materials and Methods: In order to induce hyperthermia, a number of 22-day-old male rats were placed in a 45 °C water tank for 4 minutes. Then, based on the four-stage scale, the animals which showed seizure signs were divided into 4 groups. After this stage, ten pups from the groups, which had hyperthermia and seizure, were selected for further investigations. The animals which presented no seizure behaviors were taken as hyperthermia without seizure (n=10) group. To control the effects of environmental stress a sham-control group consisting 10 rats were also included in the study.  Results: A significant elevation in the animals' body temperature in all groups was observed in comparison to the sham controls (P<0.05).No mortality was seen in the sham-control, hyperthermia without seizure, and 1st seizure stage groups., But 10% in each of the 2nd and 3rd seizure stage groups and 30% in the 4th group were died. Duration of seizure in the groups II, III, and IV was 89.46, 121.57, and 198.49 seconds, respectively. Conclusion: Hot water bath model seems to be an efficient method to induce febrile seizure in lab animals, and the interested researchers can consider it.